TREMORS, TRAGEDY AND HUMAN TRIUMPHS – CMH RAWALPINDI: Tremors, Tragedy and Human Triumphs - Nadeem, Ahmad; Khan, Viqar Ahmed; Ahmed, Tauqeer; Sheikh, Irfan Ali (Pakistan Armed Forces Medical Journal, 2006)
Introduction Mankind has seen many disasters and the history is full of wide spread destructions resulting from floods, famines, storms, Tsunami, Hurricanes and Earthquakes of all the natural calamities, earthquakes are the most devastating physically and psychologically. There can be nothing more terrorizing for the human psyche than a disaster in the form of major earthquake giving an inventory of colossal loss of life, livelihood and property, creating ruins leaving no place of solace to console. The earthquake of Tangshan, China in 1976 is considered the worst according to the death toll so far, which is 255, 000 but the earthquake of Oct 8th in Pakistan, God Forbid is the worst on the basis of the total area of the region affected, the degree of destruction that has taken place, the percentage of population that has been presumed dead and the number of injured people. The Oct 8th, Kashmir earthquake is also known as the Northern Pakistan earthquake or the South Asia earthquake, which was a ‘major’ seismological disturbance that covered an area over 20, 000 sq. km. The earthquake occurred at 08:50:38 Pakistan Standard Time on Oct 8th 2005 with the epicenter in the Pakistan Administered region of the disputed territory of Kashmir. It was registered 7.6 on the Richter (moment magnitude) scale making it one of the major earthquakes. Northern Pakistan has now become a part of the high risk level which means earthquakes can take place anytime in the near future because of which a large area of land would be left abandoned. Rehabilitation and Construction pose a greater challenge to the authorities due to its extent of destruction and the terrain of the region.